Implementation and Challenges of Emission Trading Mechanisms in Sustainable Supply Chain Management: A Bibliometric-Based Systematic Literature Review of the Manufacturing Sector - Putri Aliya Gunawan (International Journal of Business and Management Technology in Society, 2025)
Purpose – The increasing pressure to reduce carbon emissions has made emissions trading mechanisms a crucial policy instrument in Sustainable Supply Chain Management (SSCM), particularly in the manufacturing sector. This study aims to systematically examine the implementation of emissions trading mechanisms in manufacturing supply chains and identify key challenges and mitigation strategies related to the cost-emissions trade-off. Methodology – This study employed a mixed-methods approach, combining bibliometric analysis and a systematic literature review (SLR) based on the PRISMA framework. Data were obtained from the Scopus database, comprising 227 journal articles published between 2001 and 2024. Findings – The findings reveal a paradigm shift from static models toward dynamic, data-driven, and multi-objective approaches. Moreover, the results confirm that the cost–emission trade-off is not inherent but is shaped by model design, power structures within supply chains, and the alignment of policy frameworks with managerial capabilities. Originality – This study offers original insight by integrating bibliometric mapping with a systematic qualitative synthesis to examine the implementation and challenges of emission trading mechanisms within sustainable supply chain management in the manufacturing sector. Research limitations – Articles analyzed in this study are limited to publications in Scopus database during 2001-to-2024 time span. Practical implications – This study emphasizes the importance of integrating carbon policies with optimization technologies and strengthening managerial capabilities. Suggestions for further research include testing the identified models in empirical contexts across countries and industries, and developing dynamic frameworks that simultaneously incorporate policy uncertainty, actor behavior, and technological evolution.